C−C Coupling through Nitrogen Deletion: Application to Library Synthesis. Issue 4 (4th January 2023) - Holovach, Serhii; Melnykov, Kostiantyn P.; Poroshyn, Illia; Iminov, Rustam T.; Dudenko, Dmytro; Kondratov, Ivan; Levin, Mark; Grygorenko, Oleksandr O.
Abstract: Invited for the cover of this issue are Oleksandr Grygorenko and his Ukrainian colleagues at Enamine Ltd., Taras Shevchenko National University of Kyiv, National Academy of Sciences of Ukraine, and ChemSpace, as well as Mark Levin at the University of Chicago. The image depicts application of a nitrogen‐deleting anomeric amide to parallel C(sp 3 )–C(sp 3 ) coupling. Read the full text of the article at 10.1002/chem.202203470 . Abstract : " The main idea behind this study was to bring "nitrogen deletion" chemistry into production of compound libraries, and it was successfully done through formal C(sp 3 )–C(sp 3 ) coupling of "benzylic" amines and (hetero)aromatic aldehydes ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202203470 ).